ATRIBUT DAN DISAIN PEMBELAJARAN PERILAKU PROFESIONAL (PP) DALAM PENDIDIKAN DOKTER DI INDONESIA - , WIWIK KUSUMAWATI, Prof. Dr. dr. Soenarto Sastrowijoto, Sp.THT (K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction: Professional Behaviour (PB) in medical education nowadays is facing more complicated problems as an impact of the rapid development of technology. These problems also emerge in ethical aspect such as the widespreading of cheating habit and plagiarism. To anticipate this threat, the development of PB needs to be incorporated in the whole scheme of medical education. This research aims to identify the attributes and to develop a model of PB learning design to be applied in medical education in Indonesia. Method: This research adopted both qualitative and quantitative approach. At stage I, this research attempts to identify the attributes of PB through a Focused Group Discussion (FGD), interview and literature study. Stage II is focused on the development of PB learning model. This is done through the development of a prototype based on the result of stage I and literature study, followed by a validation process by a panel of experts. Stage III is focused on the testing and evaluation of PB learning model, and this involves a case study-based trial at School of Medicine and Health Sciences of Universitas Muhammadiyah Yogyakarta. Result: As many as 34 attributes of PB are found in medical education in Indonesia, consisting of 5 attributes from 4 sources, 10 attributes from 3 sources, 10 attributes from 2 sources, 9 attributes from 1 source. Attributes of religiosity and spirituality are highly typical in Indonesian context. Evaluated using academic integrity questionnaire, the experimental implementation of PB learning model on the attributes of honesty, integrity, responsibility, respect and altruism showed that: 1) PB learning through group discussion method with a movie trigger followed by a self reflection and panel of experts was found to significantly influence the studentsâ perception on the level of sanction (p = 0,0001)